Pengendalian Persediaan Bahan Baku UMKM Es Teh Klasik Balikpapan Menggunakan Metode EOQ dan POQ - Zulmy, Ahmad Nijar; Harits, Dimaz; Kurnia, Wahyu Ismail; Ari Andriyas Puji (SURYA TEKNIKA, 2024)
Es Teh Klasik MSMEs are often short of key raw materials, such as cups and tea, which hampers production and leads to loss of potential sales. Inventory control is done traditionally so that stock outs often occur before the next procurement. This study analyzes the raw materials that are often short and the best control method using ABC Classification as well as the EOQ and POQ methods. Category A raw materials include cups, tea, sugar, plastic bags, and straws. The analysis shows that the EOQ method is more efficient for cup and tea, with costs of Rp 571,512 and Rp 529,943. While POQ is more efficient for plastic bags. EOQ also determines the ideal ordering frequency, for example for cup cups, 10 times per month with 5 packs per order, safety stock of 2 packs, and reorder point when 3 packs remain.